Efficacy of entomopathogens against Thaumatotibia leucotreta under laboratory conditions. Issue 5 (3rd April 2021) - Steyn, Vernon M.; Malan, Antoinette P.; Addison, Pia
Abstract: False codling moth (FCM), Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae), is a priority pest on citrus, stone fruit, and table grapes. Current control focuses on the adult stage; however, each stage of the life cycle of the insect should be targeted. The potential of local biocontrol agents against FCM immature stages was investigated. Several entomopathogenic nematode (EPN) and entomopathogenic fungus (EPF) species were identified from soil samples collected from orchards and vineyards throughout the Western Cape province in South Africa. The eggs were proven to be susceptible (30–65%) to several EPN species, at 200 infective juveniles (IJs) per 50 µl. Xenorhabdus indica, the symbiotic bacterium of Steinernema yirgalemense Nguyen et al., caused significantly more mortality than the control. The EPNs were highly virulent against the FCM larvae, with S. yirgalemense causing 100% mortality in all trials. Metarhizium robertsii (78%), M. anisopliae (50%), and Beauveria bassiana (75%) caused high mortality in FCM larvae. The fully formed pupae were the most resistant of the immature stages, with the EPNs causing low mortality at 100 IJs per insect. As the FCM larvae were highly susceptible to S. yirgalemense and M. robertsii under laboratory conditions, they should be further tested, separately and in combination, in field conditions to illustrate the benefits of including them in a FCM‐IPM programme. Abstract : False codling moth (FCM), Thaumatotibia leucotreta (Lepidoptera: Tortricidae), is a priority lepidopteran pest in South Africa. Eggs of FCM proved to be susceptible (30–65%) to the entomopathogenic nematode Steinernema yirgalemense (100% mortality). FCM larvae were susceptible to S. yirgalemense (100% mortality), Metarhizium robertsii (78%), M . anisopliae (50%), and Beauveria bassiana (75%). As the immature FCM stages were susceptible to entomopathogens in the laboratory, field tests are needed to illustrate the benefits of including them in an IPM programme.